Barriers to healthcare access by undocumented migrants in low-and middle-income countries: A qualitative systematic review - Adnan, Salman Amirah (Department of Public Health and Family Medicine, 2024)
Undocumented migrants experience many barriers to accessing health systems around the globe. Although these barriers are well documented in the context of migration from low- and middle- to high-income countries, less attention has been paid to irregular migration within low- and middle-income countries (LMICs). This study reviewed and synthesized the available literature on barriers to accessing health systems among undocumented migrants in LMICs. Thirty-one studies published either on English, Portuguese or Spanish and published between 2013 and 2022 were included. As a growing body of evidence demonstrates, undocumented migrants are among the most vulnerable populations with access to health care services impacted by high costs, legal barriers, document requirements and unclear policy messages. By applying a health policy and systems research lens, this review found that these barriers are interrelated and further complicated by individual and institutional discrimination, xenophobia, and perceptions that undocumented migrants are less deserving and compete for local resources, among others. Delayed care and limited primary healthcare access with critical health consequences were described in all such cases. The review suggests that barriers to healthcare access require intersectoral action that needs to be guided by embedded, comprehensive evaluations to generate the knowledge that is necessary to inform effective policy-responses and implementation.